Coach autonomy support, basic need satisfaction, and intrinsic motivation of paralympic athletes - Banack, H. R.; Sabiston, C. M.; Bloom, G. A. (Research Quarterly for Exercise and Sport, 2011)
The purpose of the present study, grounded in self-determination theory, was to explore the relationship between Paralympic athletes' perceptions of autonomy-supportive coach behavior, basic psychological needs, and intrinsic motivation to know, accomplish, and experience stimulation. One hundred thirteen Canadian Paralympic athletes completed an online survey, consisting of measures of coach autonomy support; of perceptions of autonomy, competence, and relatedness; and of intrinsic motivation. Perceived coach autonomy support was a predictor of athletes' perceptions of autonomy and relatedness. Perceived competence was a significant predictor of all three forms of intrinsic motivation, while perceived autonomy was a significant predictor of intrinsic motivation to accomplish and experience stimulation. The results highlight the important relationship between coach behavior and athlete motivation in disability sport.